2011
DOI: 10.1139/t11-061
|View full text |Cite
|
Sign up to set email alerts
|

Investigating pipeline–soil interaction under axial–lateral relative movements in sand

Abstract: This paper presents results from an experimental and numerical study on the axial–lateral interaction of pipes with dense sand. A series of centrifuge tests were conducted, with a rigid pipeline displaced in the horizontal plane in a cohesionless test bed. The relative pipe–soil interaction included axial, lateral, and oblique loading events. A three-dimensional continuum finite element model was developed using ABAQUS/Standard ( Hibbitt et al. 2005 ) software. The numerical model was calibrated against experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 16 publications
5
44
1
Order By: Relevance
“…Reanalyzing 61 55 tests on model pipes and 54 on anchors, White et al (2008) showed that the same limit equilibrium provide deformation of the soil particles and location of the shear bands, tests on a wide range of 80 burial depths could not be conducted. In addition, a number of centrifuge tests were also conducted 81 using the geotechnical centrifuge at C-CORE (Daiyan et al 2011;Debnath 2016). 82…”
Section: Introduction 45mentioning
confidence: 99%
See 1 more Smart Citation
“…Reanalyzing 61 55 tests on model pipes and 54 on anchors, White et al (2008) showed that the same limit equilibrium provide deformation of the soil particles and location of the shear bands, tests on a wide range of 80 burial depths could not be conducted. In addition, a number of centrifuge tests were also conducted 81 using the geotechnical centrifuge at C-CORE (Daiyan et al 2011;Debnath 2016). 82…”
Section: Introduction 45mentioning
confidence: 99%
“…The burial depth is also expressed in normalized form using the "embedment ratio, ̃ = H/D." 87 A considerable number of physical experiments were conducted on lateral pipe-soil interaction 88 (Trautmann 1983;Hsu 1993; Daiyan et al 2011;Burnett 2015; Monroy et al 2015). Guo and 89 Stolle (2005) compiled data from 11 experimental tests on dense sand and showed that the 90 maximum dimensionless force (Nhp) increases with ̃ and decreases with an increase in pipe 91 diameter.…”
Section: Introduction 45mentioning
confidence: 99%
“…A case study [10] that involves centrifuge tests and numerical analysis performed on a rigid pipe buried in dense sand and subjected to relative axial movement is used to further validate the proposed expression. The geometry and soil properties used in the experiments are provided in Fig.…”
Section: Validation Of the Proposed Expressionmentioning
confidence: 99%
“…[2,7,10,18,21,25,26,[37][38][39]. Roy et al [33] used finite element (FE) analysis to model soil-pipe interaction in dense sand subjected to lateral ground displacements.…”
mentioning
confidence: 99%
“…In attempting to obtain the friction coefficient of pipelines, theoretical and experimental researches are available. Many researches focused on the interaction of pipe with cohesionless soil over the past several decades [2,[10][11][12][13][14][15]. Only a minority of scholars studied the pipe-clay interaction using model tests.…”
Section: Introductionmentioning
confidence: 99%